G(t)=t+5

Simple and best practice solution for G(t)=t+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for G(t)=t+5 equation:


Simplifying
G(t) = t + 5

Multiply G * t
tG = t + 5

Reorder the terms:
tG = 5 + t

Solving
tG = 5 + t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-1t' to each side of the equation.
-1t + tG = 5 + t + -1t

Combine like terms: t + -1t = 0
-1t + tG = 5 + 0
-1t + tG = 5

Reorder the terms:
-5 + -1t + tG = 5 + -5

Combine like terms: 5 + -5 = 0
-5 + -1t + tG = 0

The solution to this equation could not be determined.

See similar equations:

| 2(v-5)+7v=4 | | 2x+8=360 | | -8n= | | 10x-6x=25-25 | | 62=9g | | 53=9g | | 44=9g | | 35=9g | | 26=9g | | 17=9g | | 4x+10(x+2)=60 | | X^2-5=3x+5 | | 8=9g | | 5y=-3x+14.50 | | 5r-1=19whatisr | | 10-7y=10 | | (x+2y)(x+5y)= | | 4(2x-3)=x+7 | | 8x-12=x+7 | | 4t^2+-9t=9 | | X^2-5x+6=2x-4 | | x^2-63+2x=0 | | 600x=800x(x-.75) | | 5(12-3x)-9x=4(3-2x) | | -1.5x-5=-11 | | 7(x)=56 | | 4(3x+6)=84 | | 153=9x+5 | | 24-2x=20 | | 005(12-3y)-9x=4(3-2x) | | 2x+10=4x+54 | | 5x-1=8x-4 |

Equations solver categories